River ice monitoring of the Danube and Tisza rivers using Sentinel-1 radar data - van Leeuwen, Boudewijn; Sipos, György; Lábdy, Jenő; Baksa, Márta; Tobak, Zalán (Geographica Pannonica, 2022)
Due to extreme weather, occasionally Hungary’s main rivers and lakes grow an ice cover causing severe damage to infrastructure and increased flood hazard. During cold periods in 2017 and 2022, a dangerous layer of ice developed on the main rivers in the country. Since river ice is rare in this region, no permanent ice monitoring system is in operation. Due to their all weather capabilities, active remote sensing instruments provide a good opportunity to monitor ice coverage. ESA’s Sentinel-1 radar satellites acquire data with a relatively high spatial and temporal resolution. A method was developed to provide ice coverage information at a regular interval; depending on the satellite revisit, at least once every 5 days, but often also on a daily basis. In 2017, maps were created for sections along the Danube and in 2022 for another section of the Tisza river. The ice coverage was calculated with a spatial resolution of 10 metre and visualised with a spatial density of 100 metre along the rivers. The mapping procedure provides visual information to give a fast overview of the spatial extent of ice coverage and quantitative, tabular information for operational activities to mitigate the damage due to ice packs and ice jams.